Genome analysis of Listeria ivanovii strain G770 that caused a deadly aortic prosthesis infection. (March 2016) - Beye, M.; Gouriet, F.; Michelle, C.; Casalta, J.-P.; Habib, G.; Raoult, D.; Fournier, P.-E.
Abstract: We sequenced the genome of Listeria ivanovii strain G770, which caused a deadly infection of the thoracic aortic prosthesis of a 78-year-old man. The 2.9 Mb genome exhibited 21 specific genes among L. ivanovii strains, including five genes encoding a type I restriction modification system and one glycopeptide resistance gene.